Planetary period oscillations in Saturn's magnetosphere: Coalescence and reversal of northern and southern periods in late northern spring. Issue 10 (25th October 2016) - Provan, G.; Cowley, S. W. H.; Lamy, L.; Bunce, E. J.; Hunt, G. J.; Zarka, P.; Dougherty, M. K.
Abstract: We investigate planetary period oscillations (PPOs) in Saturn's magnetosphere using Cassini magnetic field and Saturn kilometric radiation (SKR) data over the interval from late 2012 to the end of 2015, beginning 3 years after vernal equinox and ending 1.5 years before northern solstice. Previous studies have shown that the northern and southern PPO periods converged across equinox from southern summer values 10.8 h for the southern system and 10.6 h for the northern system and near coalesced 1 year after equinox, before separating again with the southern period 10.69 h remaining longer than the northern 10.64 h. We show that these conditions ended in mid‐2013 when the two periods coalesced at 10.66 h and remained so until mid‐2014, increasing together to longer periods 10.70 h. During coalescence the two systems were locked near magnetic antiphase with SKR modulations in phase, a condition in which the effects of the generating rotating twin vortex flows in the two ionospheres reinforce each other via hemisphere‐to‐hemisphere coupling. The magnetic‐SKR relative phasing indicates the dominance of postdawn SKR sources in both hemispheres, as was generally the case during the study interval. In mid‐2014 the two periods separated again, the northern increasing to 10.78 h by the end of 2015, similar to the southern period during southern summer, while the southern period remained fixed near 10.70 h, well above the northern period during southern summer. Despite this difference, this behavior resulted in the first enduring reversal of the two periods, northern longer than southern, during the Cassini era. Key Points: We examine Saturn's planetary period oscillations (PPOs) in magnetic and SKR data over 2013‐2015 North and south periods near coalesced from mid‐2013 to mid‐2014 increasing from 10.66 to 10.70 h North period then increased to 10.78 h resulting in a reversal in periods that endured to end 2015